Feasibility of biochar technology to support the sustainable intensification and decarbonization of cocoa production in West-Africa - Pulleman, Mirjam; Hougni, Deo-Gratias; Rahn, Eric; Barrio, Julian; Coppus, Ruben; Nguyen, Thuy Thanh; Roobroeck, dries; Talsma, Tiffany (2024)
Decarbonization represents a major challenge for global commodity value chains, including cocoa. As biochar is increasingly presented as an effective carbon removal technology, it has attracted the attention of the chocolate industry. Moreover, potential agronomic and environmental benefits of biochar production and its utilisation in tropical soils could contribute to sustainable intensification of cocoa cultivation. Yet, scaling of biochar technologies has not yet been observed. We therefore explored the technical and environmental feasibility of biochar production in the context of smallholder cocoa farming in Ivory Coast and Ghana, responsible for more than 60% of the global supply. We combined extensive literature review with expert interviews to inform a carbon accounting model. The model calculates a carbon balance associated with different scenarios of biochar production and incorporation in soil under cocoa cultivation, compared to a baseline representing current practices. Next, we synthesised practical challenges and opportunities for adoption and scaling, based on the same interviews. The carbon removal potential of biochar is fully realised only if its production is coupled with bioenergetic applications that displace GHG emissions from non-sustainably sourced energy. In the most plausible scenario, the woody pruned residues and cocoa pod husks are gasified in improved cookstoves yielding ~20% biochar. Largest uncertainties arose from the use of fossil fuel powered machines for feedstock crushing, biochar grinding, and transport from and to conversion site. Additional challenges for scaling include labour demand, feedstock availability, application rates, equipment reproducibility at local scale, and lack of proven yield response. Opportunities include biochar co-composting in nutrient deficient soils, and application of biochar to seedlings exposed to drought conditions (nursery and replanting) and in light-textured, acidic soils. The study highlights consolidated knowledge and priorities for further research. Low technology readiness for current cocoa farmers, further exacerbated by economic challenges, will need to be addressed for farmers and industry to benefit from the opportunities of biochar.